Graduation from cash transfer programmes: Insights from Tanzania - Winnie C. Muangi (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2024)
This working paper examines the prevalence of humanitarian crises in Tanzania, their role in perpetuating poverty cycles, and how poverty graduation programmes mitigate these effects by building the resilience of ultra-poor households. We utilize a mixed-methods approach, comprising desk reviews, in-depth interviews, and a survey, to understand poverty graduation programmes as well as the efforts of the Tanzania Social Action Fund in enhancing beneficiary resilience through targeted interventions, particularly livelihood enhancement initiatives such as the Community Savings and Investment Promotion programme. Additionally, we assess the perceptions of poverty graduation among beneficiaries, local government authorities, and programme implementers, identifying key factors that influence beneficiaries' ability and desire to graduate from assistance programmes. The findings highlight the importance of implementing tailored, context-specific interventions that account for beneficiaries' demographic characteristics, social networks, and economic activities. Drawing on lessons from successful models such as BRAC's Ultra-Poor Graduation Programme, we provide recommendations for refining Tanzania's graduation strategy to ensure sustainable poverty reduction and economic resilience.
Keywords: D91; H53; I38; Q54; 330; graduation; cash transfers; humanitarian crises; Tanzan